Dietas suplementadas com arginina para fêmeas suínas hiperprolíferas no período final da gestação e na lactação - Lima, Daniele de (2010)
The experiment was conducted at the pig farm of DanBred (DB) breeding company located in Morada Nova de Minas - MG, aiming to evaluate levels of arginine supplementation in diets of hiper-prolific sows from 90 days of gestation and during lactation on reproductive parameters. Were selected one hundred and twenty sows between second and seventh parity order (genetic DB), with number of born pigs in previous farrowing of more than 12 piglets. The experiment was divided into two periods: the first begun at 90 days of gestation to farrowing, and second from birth to weaning (22 days). The design was randomized blocks (parity order) with four treatments (inclusion of levels of arginina - 0; 0,5; 1,0 and 1,5%) and three blocks with an average of 40 sows each. The total number of piglets born, piglets born alive, mummified, stillborn, litter weight born, litter weight born alive, piglet weight born and live, placental weight and placental efficiency were not affected by different levels of arginine. Significant quadratic effect of litter weight and daily weight gain piglet in the first week of lactation were observed, 11% higher with supplementation of 1,0% arginine as control diet. At weaning, the sows that received this level of arginine presented one weaned piglet more. It was observed a quadratic effect of arginina levels on litter weight at 22 days, being 12% higher also with supplementation of 1%. In conclusion, the supplementation of diets for hiper-prolific sows with arginine is important for improving the reproductive efficiency of breeding. The addition of 1.0% of this amino acid in diets containing corn, soybean meal and wheat bran from 90 days of gestation and during lactation increases the number of piglets weaned per sow.